Investigation on the effect of surfactants on the viscosity of graphite-water-based nanofluids - Yalcin, Gokberk; Huminic, Gabriela; Huminic, Angel; Panchal, Hitesh; Dalkilic, Ahmet Selim (ELSEVIER, 2024)
In the current experimental research, the dynamic viscosity alteration of a water-based 2 % graphite nanofluid was examined with three different surfactants: gum arabic, cetrimonium bromide, and ammonium citrate. Surfactant proportions of 5 %, 10 %, 50 %, and 100 % of 2 % graphite nanoparticle amount were chosen. Dynamic viscosity changes were measured at 10 degrees C, 30 degrees C, and 50 degrees C. The maximum dynamic viscosity was measured for the 100 % gum arabic at 10 degrees C. The relative viscosity was also measured at 10 degrees C for the 100 % gum arabic sample, which was 2.77 times that of the base fluid. Surprisingly, 2 % graphite nanofluid with ammonium citrate surfactant showed weaker stability than the surfactant-free sample. The three regression equations were placed with R-2 = 0.9896 for gum arabic, R-2 = 0.9808 for cetrimonium bromide, R-2 = 0.9927 for ammonium citrate, and compared with previously presented equations. As a result, different surfactant proportions and types can affect the nanofluid viscosity in different ways and therefore, new enlightening researches will be useful for researchers to understand surfactant behavior. The results showed that different surfactant usages could change the dynamic viscosity of nanofluids distinctly. It is expected that this research will be informative for scientists in terms of surfactant usage-viscosity relations.
Keywords: Nanofluid; Viscosity; Surfactant; Gum arabic; Cetrimonium bromide; Ammonium citrate; THERMO-PHYSICAL-PROPERTIES; CONVECTIVE HEAT-TRANSFER; THERMOPHYSICAL PROPERTIES; HYBRID NANOFLUIDS; ALUMINA-WATER; CONDUCTIVITY MODELS; DYNAMIC VISCOSITY; ETHYLENE-GLYCOL; PARTICLE-SIZE; STABILITY; Chemistry; Physics